Major Strategies on Building Production Innovation Influencing Competitive and Growth Strategies in Construction Companies - Ercan, Tugce (GAZI UNIV, 2013)
This study aims to identify the impact of two factors -growth and competitive strategies- on a set of strategies for building production innovation. A questionnaire survey was conducted to collect data from construction professionals, who were asked to rate the importance level of predicted innovation strategies on some corporate strategy combinations. Multiple analysis of variance (MANOVA) was employed to see the main and interaction effects of corporate strategies on building innovation strategies. The results indicate that growth strategies such as entering in a new a market or new project types has a greater effect on innovation strategies than competitive strategies such as cost leadership or differentiation strategies. However, the interaction effect of competitive and growth strategies together have been found to be much bigger than the effect of competitive strategies alone. The descriptive statistics of innovation strategies for different competitive and growth strategy types has also been analyzed in the study.
Keywords: Competitive strategy; growth strategy; innovation; construction company; MANOVA; Science & Technology - Other Topics